Evolution of Project Managers to Project Leaders Due to Artificial Intelligence - Singh, Manwendra (Digital Repository of Theses, 2024)
This research explores the evolving role of project managers in response to the integration of artificial intelligence (AI) into project management practices. Traditionally, project managers were primarily tasked with administrative functions, but the rise of AI is ushering in a transformation that demands a shift towards strategic leadership. The objectives of this study are to investigate the impact of AI integration on project manager’s evolving roles. Key research questions delve into workload changes, required skill sets, perceptions of leadership transformation, perceived benefits and challenges, and the attitudes of project team members. The findings of this research affirms that the increasing incorporation of AI in project management is indeed driving a fundamental transformation in the role of project managers. They are transitioning from task-focused managers to Project Leaders who play a pivotal role in guiding projects towards achieving broader organizational objectives. This research also sheds light on the changing landscape of project management in the era of AI.